2011
DOI: 10.1105/tpc.111.087643
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Dormancy in Arabidopsis Summer Annuals Requires Parallel Regulation of DOG1 and Hormone Metabolism by Low Temperature and CBF Transcription Factors

Abstract: Summer annuals overwinter as seeds in the soil seed bank. This is facilitated by a cold-induced increase in dormancy during seed maturation followed by a switch to a state during seed imbibition in which cold instead promotes germination. Here, we show that the seed maturation transcriptome in Arabidopsis thaliana is highly temperature sensitive and reveal that low temperature during seed maturation induces several genes associated with dormancy, including DELAY OF GERMINATION1 (DOG1), and influences gibberell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
272
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(288 citation statements)
references
References 52 publications
(82 reference statements)
10
272
1
5
Order By: Relevance
“…Similarly, seeds of the Col ecotype matured at 158C were also reported to have decreased germination in response to cold stratification compared to those matured at higher temperatures (e.g. 208C) (Donohue et al, 2008;Kendall et al, 2011).…”
Section: Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, seeds of the Col ecotype matured at 158C were also reported to have decreased germination in response to cold stratification compared to those matured at higher temperatures (e.g. 208C) (Donohue et al, 2008;Kendall et al, 2011).…”
Section: Temperaturementioning
confidence: 99%
“…This takes the form of sensing the maternal environment (light, nitrate and temperature) (Sawhney et al, 1985;Alboresi et al, 2005;Kendall et al, 2011;Kendall and Penfield, 2012;Penfield and Springthorpe, 2012;He et al, 2014;Huang et al, 2014) and the environment of the soil seed bank (light, nitrate and temperature) (Footitt et al, 2011(Footitt et al, , 2013Finch-Savage and Footitt, 2012;Penfield and Springthorpe, 2012). This enables seeds to use environmental signals to determine the time and place of seed germination and subsequent seedling emergence (Baskin and Baskin, 1998;Finch-Savage and LeubnerMetzger, 2006;Footitt et al, 2011Footitt et al, , 2013Footitt et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For seed dormancy, analysis of Arabidopsis natural genetic variation has led to the cloning of AtDOG1 as the first specific seed dormancy gene (Bentsink et al, 2006) and has been shown to be important for local adaptation to different environments (Huang et al, 2010;Chiang et al, 2011;Footitt et al, 2011;Kendall et al, 2011;Kronholm et al, 2012). Homologs of the AtDOG1 gene are also known for the Brassicaceae species B. rapa (BrDOG1) and Lepidium sativum (Lesa-DOG1; Graeber et al, 2010).…”
mentioning
confidence: 99%
“…Recent work shows that the AtDOG1 protein accumulates during seed maturation and, unlike the transcript, remains stable throughout imbibition of Arabidopsis seeds . The mother plant environment, especially the ambient temperature during seed development, controls AtDOG1 gene expression during seed maturation as well as the seed dormancy status (Kendall et al, 2011;Nakabayashi et al, 2012).…”
mentioning
confidence: 99%